Identifikasi kutu daun yang berasosiasi dengan tanaman jeruk - Syarni, Elisa; Taufik, Muhammad Taufik; Yusuf, Dewi Nurhayati; Nurulita, Sari; Miftakhurohmah, Miftakhurohmah; Botek, Muhammad; HS, Gusnawaty; Hikamwaty, Aisyah (Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Aphids are polyphagous insects commonly found on various plants, including citrus plants. The association between aphids and citrus plants plays a role as pests and vectors of citrus plant diseases, particularly Citrus tristeza virus (CTV). Various aphid species have been reported as CTV vectors, including Aphis gossypii, Toxoptera aurantii, and T. citricidus. So far, no information has been on aphid species associated with citrus plants in Southeast Sulawesi. Therefore, this study aimed to identify aphid species associated with citrus plants. The research method used was observation and collection of aphids found colonizing citrus plants. The collected aphids were then brought to the laboratory for detection using the polymerase chain reaction (PCR) technique. The study results showed that the aphid species associated with citrus plants was Aphis citricidus. The PCR technique successfully detected the genome of aphid vector samples from Konawe and South Konawe (700 bp). This information is a fundamental basis for controlling CTV in mainland Southeast Sulawesi.